Environmental Sustainability of Social and Executive Events in Ciudad Juárez, Mexico - González Herrera, Manuel Ramón (Springer Nature, 2024)
The results of the diagnostic and proposal study are presented to promote good environmental sustainability practices in enterprises that organize and celebrate social and executive events in hotels, restaurants, and halls in Ciudad Juárez, and thus offer a contextualized strategic agenda at a local level, which promotes environmental positioning and more outstanding environmental leadership. The methodological design was qualitative–quantitative, cross-sectional, and applied, using mixed information sources; among the empirical methods were participant observation, document analysis, surveys, and interviews. At the theoretical level, analytical–synthetic, historical–logical, systemic–structural methods, and conceptual models were used. It is concluded that there is a lack of sensitivity on the part of the enterprises that promote events in the face of the negative environmental impact they generate and that it will be necessary to project good practices of environmental sustainability in all tourist enterprises that organize and celebrate social and executive events in hotels, restaurants, and halls in this city.